Barriers and policy enablers for solar photovoltaics (PV) in cities: Perspectives of potential adopters in Hong Kong. (September 2018) - Mah, Daphne Ngar-yin; Wang, Guihua; Lo, Kevin; Leung, Michael K.H.; Hills, Peter; Lo, Alex Y.
Abstract: The rapid decline of solar PV costs and the urgency to develop effective post-Fukushima climate/energy plans in recent years have led to an upsurge of policy interest in deploying solar in international megacities including New York, Tokyo and Singapore. Nonetheless, overcoming barriers to large-scale uptake of urban solar PV remains under-explored. This study conducted 57 face-to-face interviews with potential solar PV adopters from the residential, institutional, and commercial sectors in Hong Kong, to understand perceived barriers and policy preferences. We found that firstly, most interviewees perceived high upfront costs and long payback period as primary barriers. Secondly, a reduced payback period is effective in improving their attitude towards installing solar. A majority of the residential interviewees shifted away from the "low level of interest" group to higher levels of interest if payback periods could be reduced from 35 years (business-as-usual scenario) to 8 years. Thirdly, potential PV adopters had different policy preferences. While residential interviewees indicated a strong preference for subsidies, institutional interviewees leaned towards regulatory measures, and commercial interviewees preferred feed-in-tariffs. Our findings suggest that the Hong Kong government needs to adopt the enabling framework developed in this study to effectively steer, nurture, and regulate PV deployment.